Crossed - Condie, Ally (New York : Scholastic, 2011)
Seventeen-year-old Cassia sacrifices everything and heads to the Outer Provinces in search of Ky, where she is confronted with shocking revelations about Society and the promise of rebellion.
Keywords: Dystopia -- Fantasy Fiction